Desafios e enfrentamentos no processo de interiorização da Universidade Federal da Paraíba (2007 – 2012): uma análise dos cursos criados pelo Reuni a partir das demandas no Campus de Areia - Nascimento, Lindalva Gouveia (2017)
The public higher education policies implemented in Brazil in recent years are provoking significant structural changes in Brazilian society; however, the asymmetries between regions, social groups, vocational training, education have a historical basis and the challenge of reducing these Fundamental access to quality education for most of the population at all levels of training, but for changes of this magnitude the government will take decades to solve, since it will dispense with several actions in different aspects. The expansion of higher education is one of the focuses of public policies in education. It is observed the intensification of this process that has been implemented in the country through several actions, which we highlight in this research in the thematic field of the policy of expansion of higher education at the Federal University of Paraíba, in its institutional context, in order to understand the Political dimension of this action by turning to the courses created in Campus II, located in Areia - Paraiba, based on the educational policy created by the federal government entitled "Support Program for Restructuring and Expansion of Federal Universities" - Reuni, created through Of Decree no. 6,096 of April 24, 2007, with execution for the period of 2007 to 2012. The course we have followed allowed us to understand the democratization of higher education in federal public universities, based on the opening of vacancies made possible by this program, Whose initiative was due to the government of former president Luis Inácio Lula da Silva. To support the research, we use different documentary instruments, as well as interviews and conversations with UFPB representatives. The research evidenced that the creation of the Veterinary Medicine and Chemistry Courses met the demands of Campus II that yearned for academic formation. In view of the subsidies of the analysis, the study showed that the expansion policy marked a process of reorganization of federal universities justified by the political perspective of democratizing education, while at the same time fulfilling its social functions. The results of the study pointed out that the expansion policy of the UFPB converges to open vacancies in the UFPB by increasing opportunities for access to the courses created from the Reuni.